Biocultural Design: Harvesting Manomin with Wabaseemoong Independent Nations - Valeria Kuzivanova; Iain J. Davidson-Hunt (Ethnobiology Letters, 2017)
This essay describes how biocultural design (BD) was utilized to develop a manomin (wild rice, Zizania palustris) harvest camp and the prospect of this approach to implement the principles reflected in recent calls for an Ethnobiology V. In this case, BD brought together knowledge, practices, and innovation within an intentional process of co-design to respond to the specific community aspirations of restoring relationships with manomin. The paper provides an overview of the benefits and challenges of using the practice of BD to re-establish wild rice harvesting. The information presented here is part of a larger initiative to restore manomin habitats, harvest practices, and consumption being undertaken by Wabaseemoong Independent Nations, Northwestern Ontario, Canada.